Impact of Antibiotics and Proton Pump Inhibitors on Efficacy and Tolerance of Anti-PD-1 Immune Checkpoint Inhibitors - Giordan, Quentin; Salleron, Julia; Vallance, Catherine; Moriana, Clothilde; Clement-Duchene, Christelle (Frontiers in Immunology, 2021)
Background The use of antibiotics (ATB) and proton-pump inhibitors (PPI) alters the composition and diversity of the gut microbiota, which can influence the immune system, consequently interfering with response to anti-PD1 immune checkpoint inhibitors (ICI). We assessed the impact of ATB and/or PPI use on the efficacy and safety of ICI. Methods Two hundred twelve patients treated with anti-PD1 ICI for non-small cell lung carcinoma, melanoma, upper airway & digestive tract carcinoma or renal cell carcinoma were retrospectively included. Patients having received ATB within 60 days before ICI initiation were included in the ATB+ group. Patients having received PPI within 30 days before ICI initiation were included in the PPI+ group. Four groups were thus considered: ATB-/PPI-, ATB+/PPI-, ATB-/PPI+, ATB+/PPI+. Response rate was assessed by RECIST v1.1. Overall survival (OS), progression-free survival (PFS) and adverse events, recorded using Common Terminology Criteria for Adverse Events Version 5, were compared using inverse probability of treatment weighting to account for selection bias. Results PFS at 6 months was 56.7 %, 95%CI (49.6%; 63.2%) and 47.2 %, 95%CI (39.8%;54.1%) at 12 months. OS was 81.6%, 95%CI (75.6%; 86.2%) at 6 months, and 69.4%, 95%CI (61.9%;75.7%) at 12 months. Compared to ATB-/PPI- group, PFS was lower for the ATB+/PPI- group [Hazard ratio (HR) 1.90, 95%CI (1.41;2.57)] and the ATB-/PPI+ group [HR 1.51, 95%CI (1.11;2.05)], and lowest in the ATB+/PPI+ group [HR 3.65, 95%CI (2.75;4.84)]. For OS, the use of ATB alone or PPI alone or in combination was a risk factor for death, with each increasing HR values by a similar magnitude, and the combination of ATB and PPI did not increase risk further. AEs were observed in 78 cases (36.8%) with no significant impact of ATB or PPI use. Conclusions This study reveals that ATB and/or PPI use can alter response to anti-PD1 ICI, and the prognosis of cancer patients. The microbiota mechanisms involved in the response to ICI should be investigated to optimize patient management.